2015
DOI: 10.1111/jac.12129
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Responses of Plantain (Plantago lanceolata) and Chicory (Cichorium intybus) to Water Stress and Defoliation Frequency

Abstract: Plants are often subjected to periods of water stress. There are little data examining the effect of water stress on the forage species Plantago lanceolata and Cichorium intybus. In two pot experiments with P. lanceolata and C. intybus, morphological responses under optimum, dry, and very‐dry water treatments with weekly, fortnightly and 3‐weekly defoliation intervals and physiological responses under optimum and very‐dry water treatments were measured. A third experiment compared the rooting depths of P. lanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…Bandeira et al (2011) observed that plants submitted to deficit irrigation presented SDM 31.3% lower than the plants without water restriction. In the study of Cranston et al (2016) a greater leaf mass was obtained in chicory plants submitted to moderate and severe deficit irrigation in comparison to the fully irrigated plants, suggesting larger leaves, a result that is similar to the ones reported in the present study.…”
Section: Chicory Yield In Response Of Deficit Irrigationsupporting
confidence: 90%
See 2 more Smart Citations
“…Bandeira et al (2011) observed that plants submitted to deficit irrigation presented SDM 31.3% lower than the plants without water restriction. In the study of Cranston et al (2016) a greater leaf mass was obtained in chicory plants submitted to moderate and severe deficit irrigation in comparison to the fully irrigated plants, suggesting larger leaves, a result that is similar to the ones reported in the present study.…”
Section: Chicory Yield In Response Of Deficit Irrigationsupporting
confidence: 90%
“…Although the purpose of growing chicory was different than in the present study, the studies performed by Cranston et al (2016) and Patel et al (2000) present an analysis of chicory yield during periods of water deficit, analyzing shoots fresh mass, number of leaves per plant, leaf mass and root dry mass. Apart from the studies mentioned above and some other research in literature about irrigation and chicory yield, there are some studies regarding the deficit irrigation influence on plants of the same family, such as lettuce (Bandeira et al, 2011;Santos and Pereira, 2004).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Under water deficit conditions, many physiological parameters such as chlorophyll contents, tissue water content and membrane stability are generally measured as signs of improved plant growth and development (Razzaq et al 2013). However, physiological and morphological adaptations of plants to water stress conditions may vary among species or even among the cultivars/lines of the same crop (Cranston et al 2016). However, purposeful use of irrigation is essential because all ontogenic stages are not equally susceptible to drought stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…While we did not manage to secure a contribution on these species, there is a growing body of information on the agronomy, physiology, and animal performance expectations for these crops [11][12][13][14]. Other forage herbs are also potentially valuable.…”
Section: Studies Of Forage Legumes and Forage Herbsmentioning
confidence: 99%